Characteristics and Performance of Cement Modified–Base Course Material in Western Australia - Jitsangiam, Peerapong; Chummuneerat, Suphat; Phenrat, T.; Nikraz, Hamid (American Society of Civil Engineers (ASCE), 2014)
Hydrated Cement Treated Crushed Rock Base (HCTCRB) is produced by adding 2% Portland cement (by mass) to a standard crushed rock base (CRB) at an optimum moisture condition. The unique production process for HCTCRB is different from that of a common cement-treated base in that a re-mixing process is performed after the hydration of cement, preventing cementitious bonding to maintain the unbound material characteristics with an improvement in material engineering properties. This paper presents the resilient modulus (MR) and permanent deformation (PD) characteristics of HCTCRB after variable hydration periods, water addition during compaction and dryback. The difference in material hydration periods affected the performance of HCTCRB. However, in this study, a consistent performance trend with various hydration periods could not be found. Moisture contents have major influence on the properties of HCTCRB. The results indicate that a higher moisture content gives a more increase in PD and a more decrease in MR of this material. Addition of more water during compaction caused inferior PD and MR performance even though the samples achieved a higher dry density. A dryback process to achieve a dryer condition can improve material performance. After samples were subjected to a dryback process, it was found that samples prepared by adding water during compaction showed a decrease in material performance comparing to samples that were compacted without additional water. Thus, the amount of water addition to mixes during compaction must be controlled.